Assessment of Antarctic Amplification Based on a Reconstruction of Near-Surface Air Temperature - Jiangping Zhu; Aihong Xie; Xiang Qin; Bing Xu; Yicheng Wang (Atmosphere, 2023)
Polar amplification has been a research focus in climate research in recent decades. However, little attention has been paid to Antarctic amplification (AnA). We have examined the variations in annual and seasonal temperature over the Antarctic Ice Sheet and its amplification based on reconstruction covering the period 2002–2018. The results show the occurrence of annual and seasonal AnA, with an AnA index greater than 1.39 with seasonal differences, and that AnA is strong in the austral winter and spring. Moreover, AnA displays regional differences, with the greatest amplification occurring in East Antarctica, with an AnA index greater than 1.51, followed by West Antarctica. AnA is always absent in the Antarctic Peninsula. In addition, amplification in East Antarctica is most conspicuous in spring, which corresponds to the obvious warming in this season; and the spring amplification signal is weakest for West Antarctica. When considering the influence of the ocean, the AnA becomes obvious, compared to when only the land is considered. Southern Annular Mode (SAM), surface pressure and westerlies work together to affect the temperature change over Antarctica and AnA; and SAM and surface pressure are highly correlated with the temperature change over East Antarctica. The picture reflects the accelerated changes in Antarctic temperature.